Study of the Role of Social-Media on Consumer Desire to Shop in E-Commerce - Rudy Irwansyah; Supiah Ningsih (International Journal of Economics (IJEC), 2023)
Social media now has a very important role in people's lives. Social media has a function as a tool for interacting and socializing between one individual and another. And this can be done online, which gives humans the possibility to interact without space and time limitations. Social media has a very important role in the economic industry. Especially in shopping in e-commerce. This research was conducted to find out how much influence social media has on consumers' decisions to buy the goods they want. This research method by analyzing data from methods such as questionnaires, observation and also literature study. Besides that, the quantitative method is the method used in this research. Testing the validity, reliability and also the coefficients is one way of analyzing the data obtained to see the influence of social media on consumer decisions. There is a significant influence exerted by social media on consumers' desire to shop at E-Commerce.